LEXICAL-STYLISTIC DEVICES IN THE ENGLISH LANGUAGE AND THEIR EXEMPLARY ANALYSIS - Goncha Ahmadova (Progress in Science, 2025)
Lexical-stylistic devices are among the main elements that express the artistic and aesthetic potential of a language. Through these devices, a speaker or writer can convey thoughts more effectively, vividly, and emotionally. The use of such devices in English, particularly in literature, journalism, and everyday speech, demonstrates the richness and creative capacity of the language. Lexical stylistics examines not only the semantic but also the stylistic layer of language, revealing its functional and aesthetic roles. In this context, the study of lexical-stylistic devices constitutes one of the main directions of linguistics, translation studies, literary criticism, and stylistics. These devices are not only a form of expression but also carriers of culture, and they may be evaluated differently depending on the context. Modern stylistics, by considering the role of these devices in shaping the style of the text, the author’s position, and the emotional atmosphere, allows for a deeper analysis of their function. At the same time, the study of stylistic devices has great methodological significance for language learners, as it helps to expand the expressive possibilities of the language and increase the impact of writing. These devices enable writers and poets to deepen word meanings, thus delivering their intended message more powerfully and emotionally to the reader. Lexical-stylistic devices in English strengthen both the rhythm and the visual and emotional impact of the text. This paper will focus on some of the most commonly used lexical-stylistic devices in English, providing explanations and examples for each. The aim is to help understand how these devices enhance the aesthetic impact of language and influence the reader.